Orthodontic approach to treat complex hypodontia using miniscrews in a growing patient - Renato Barcellos Rédua; Paulo Cesar Barbosa Rédua; Carlos Eduardo de Almeida Ferreira; Adriana de Oliveira Lira Ortega (Dental Press Journal of Orthodontics, 2015)
This article reports orthodontic treatment of a case of hypodontia of five premolars in an 11-year-old female patient with a positive tooth size-arch length discrepancy in both dental arches. The patient had a straight profile with balanced facial growth. Setup manufacture revealed the possibility of achieving ideal occlusion by mesializing permanent molars up to 15 mm, in addition to keeping a primary molar in the dental arch. With the aid of absolute anchorage, the proposed mechanics was performed and the occlusion predicted in the setup was achieved, while profile and facial growth pattern were maintained. The use of miniscrews for extensive orthodontic movements was successful. Furthermore, one primary molar was extensively mesialized. The indication of gingivoplasty to correct gingival smile proved effective. This is considered a useful technique for orthodontists.